1995
DOI: 10.1038/374693a0
|View full text |Cite
|
Sign up to set email alerts
|

The structure of trp RNA-binding attenuation protein

Abstract: The crystal structure of the trp RNA-binding attenuation protein of Bacclius subtilis solved at 1.8 A resolution reveals a novel structural arrangement in which the eleven subunits are stabilized through eleven intersubunit beta-sheets to form a beta-wheel with a large central hole. The nature of the binding of L-tryptophan in clefts between adjacent beta-sheets in the beta-wheel suggests that this binding induces conformational changes in the flexible residues 25-33 and 49-52. It is argued that upon binding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
277
2
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(289 citation statements)
references
References 33 publications
9
277
2
1
Order By: Relevance
“…The crystal structures of tryptophan-activated Bacillus stearothermophilus TRAP in binary complex with tryptophan (1QAW) (12) and in ternary complex with tryptophan and RNA (1C9S) (13,14) reveal an oligomer of eleven identical subunits related by an eleven-fold rotational axis of symmetry. The structure is comprised of eleven anti-parallel beta-sheets, with each sheet consisting of three strands from one subunit and four strands from the neighboring subunit ( Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structures of tryptophan-activated Bacillus stearothermophilus TRAP in binary complex with tryptophan (1QAW) (12) and in ternary complex with tryptophan and RNA (1C9S) (13,14) reveal an oligomer of eleven identical subunits related by an eleven-fold rotational axis of symmetry. The structure is comprised of eleven anti-parallel beta-sheets, with each sheet consisting of three strands from one subunit and four strands from the neighboring subunit ( Figure 1).…”
mentioning
confidence: 99%
“…The structure is comprised of eleven anti-parallel beta-sheets, with each sheet consisting of three strands from one subunit and four strands from the neighboring subunit ( Figure 1). The tryptophan ligand is completely buried between the beta-sheets at the interface between subunits in a cavity that is largely apolar with a few polar side-chain and backbone moieties making hydrogen bond contacts to the sidechain amide and backbone amino and carboxyl groups of the tryptophan (12,(14)(15)(16). The bound RNA wraps around the protein with conserved bases making specific contacts with TRAP residues (13,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The trp RNA-binding Attenuation Protein (TRAP) is an RNA-binding protein that negatively regulates expression of the tryptophan biosynthesis (trp) genes in Bacillus subtilis in response to intracellular levels of tryptophan (Gollnick, 1994;Babitzke, 1997)+ Six of the seven trp genes are clustered in the trpEDCFBA operon+ Transcription of this operon is controlled by an attenuation mechanism involving two mutually exclusive RNA secondary structures that form in the leader region 59 to the structural genes+ One of these structures is an intrinsic transcription terminator and the other overlapping structure is an antiterminator+ When activated by binding tryptophan, TRAP binds to a series of 11 triplet repeats composed of GAG or UAG that, in part, overlap a portion of the antiterminator+ TRAP binding therefore prevents antiterminator formation, which leads to formation of the terminator, and transcription halts in the leader region+ Under conditions of limiting tryptophan, TRAP does not bind RNA and the antiterminator structure is favored, allowing transcription of the operon+ TRAP also regulates translation of several genes+ By binding to the same site in the leader region of trp read-through mRNAs, TRAP induces formation of an RNA structure that sequesters the trpE ribosome binding site, thereby inhibiting translation initiation (Kuroda et al+, 1988;Merino et al+, 1995;Du & Babitzke, 1998)+ Translation of trpG, which is in the folate operon (Slock et al+, 1990;Yang et al+, 1995), and of yhaG, which is believed to encode a tryptophan transport protein (Sarsero et al+, 2000a), is also regulated by TRAP+ In these cases the TRAP binding site overlaps the ribosome binding site, and for trpG, Du et al+ (1998) demonstrated that TRAP competes directly with ribosomes for binding to this mRNA+…”
Section: Introductionmentioning
confidence: 99%
“…TRAP also regulates translation of trpP, a gene that encodes an apparent tryptophan transporter (22,29), and ycbK, a gene that shares sequence homology to known efflux protein genes (23,28). TRAP consists of 11 identical subunits arranged in a single ring (2). When activated by tryptophan, 11 KKR motifs on the perimeter of TRAP interact with multiple NAG trinucleotide repeats in target transcripts, with a preference for N of G Ϸ U Ͼ A Ͼ C, thereby wrapping the RNA around TRAP's perimeter (1,6,32).…”
mentioning
confidence: 99%